Organizational Development in the Era of Digital Transformation: A Systematic Review Using the PRISMA Framework - Dewi Praptiwi; Icha Vanida Putri; Riki Arli; Iqbal Baihaqi; C. Cedaryana (Golden Ratio of Data in Summary, 2026)
Digital transformation requires organizations not only to adopt advanced technologies but also to strengthen organizational development (OD) capabilities that support effective change management, innovation, and continuous learning. However, there is still limited synthesis of the most relevant OD strategies that enable organizations to become adaptive and sustainable in rapidly changing environments. This study aims to identify and synthesize key organizational development strategies that support digital transformation through a Systematic Literature Review guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, a structured method for systematically identifying, screening, and analyzing relevant research. The review analyzed 12 peer-reviewed articles published between 2020 and 2024 using thematic analysis. The findings reveal five major strategic themes: strengthening digital capabilities and employee competencies, redesigning technology-supported organizational structures and work processes, integrating human resource management with change-management practices, fostering agile and collaborative organizational cultures, and reinforcing digital leadership. These strategies contribute to improved organizational adaptability, accelerated technology adoption, and sustained innovation. The results indicate that successful digital transformation depends not only on technological investment but also on the development of dynamic capabilities, defined as an organization’s ability to sense opportunities, adapt, and reconfigure internal resources in response to environmental change. This study provides a structured synthesis that can guide organizations, educational institutions, and policymakers in designing effective and sustainable OD initiatives in the digital era.